ANALYSIS OF THE INFLUENCE OF GADGETS ON CHILDREN'S EMOTIONAL INTELLIGENCE - Paulina Erawati Paramita; Zulkifli Zulkifli; Firman Aziz; Dede Supendi; Mas'ud Muhammadiah (Jurnal Scientia, 2023)
The increased usage of electronic devices by children has prompted a discussion regarding its impact on emotional intelligence. According to a number of studies, children's emotional intelligence can benefit from the moderate use of electronic devices, including the improvement of social and communication skills. Therefore, the purpose of this study is to examine the positive and negative effects of technology on the emotional intelligence development of children. Utilizing a literature analysis, this study examines the impact of gadget use on children's emotional intelligence. The findings indicate that excessive or uncontrolled use can result in emotional issues such as anxiety, depression, and lack of awareness of the surrounding environment. Therefore, it is essential to limit children's gadget and ensure that they have ample access to activities that foster emotional intelligence. To maximize the benefits of device use for children, parents should play a crucial role in establishing limits and educating their children on emotional intelligence.